PERAN PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KESADARAN TOLERANSI SISWA MADRASAH ALIYAH MELALUI MEDIA QUIZZIZ : BULLYING NONVERBAL - Nurafifah, Pevi; Araniri, Nuruddin; Sabana, Agus Asri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The prevalence of nonverbal bullying in Madrasah Aliyah environments indicates a low level of tolerance awareness among students. Previous studies have discussed the role of religious values and instructional media in bullying prevention, but few have specifically examined the integration of interactive educational media into Islamic Religious Education (PAI) instruction. This research addresses that gap by introducing the novelty of using video-based Quizziz educational media in PAI learning to enhance tolerance awareness. The study aims to determine the extent to which the use of Quizziz educational videos in PAI learning influences the improvement of tolerance awareness among Madrasah Aliyah students. A quantitative approach with an experimental design was employed, focusing on grade X students at MAN 2 Majalengka. The research instruments included questionnaires and tests, which were validated for reliability and analyzed using normality, homogeneity, and independent sample t-tests via SPSS. The results revealed a significant difference between the control and experimental classes, with the latter using Quizziz educational videos showing greater improvement across four indicators of tolerance: appreciating differences, empathy, peaceful conflict resolution, and respect for the rights and dignity of others. Thus, PAI learning incorporating Quizziz educational videos is proven effective in enhancing tolerance awareness and preventing nonverbal bullying among Madrasah Aliyah students.